Fungos toxigênicos em solos de vinhas, uvas e mostos e Ocratoxina A em vinhos e sucos do Vale do Submédio São Francisco - Terra, Michelle Ferreira (2011)
Ochratoxin A (OTA) is a frequent contaminant in grapes, wines and grape juices. This toxin is considered to be one of the most hazardous mycotoxins for humans. This study was performed with the objective of evaluating the occurrence of ochratoxigenic fungi of the genus Aspergillus Section Nigri in grapes, grape must, and soil of wineries of Northeastern Brazil, as well as verify the levels of Ochratoxin A of the wines, grape juices made with the varieties present in the region. The isolation of berries and seeds was performed by the Direct Plating method in the Dichloran Rose Bengal Cloramphenicol media (DRBC). For the grape must samples, the serial dilution with superficial spreading technique was used. We selected only the specimens of the genus Aspergillus Section Nigri to produce pure cultures, which were identified through their morphologic characteristics. All the isolates obtained were tested for the potential of OTA production through the Pug Agar method. The quantification of OTA in the samples of wine and grape juices was obtained through the High Performance Liquid Chromatography (HPLC) with fluorescence detection method. Of all the isolates obtained (281), the majority (61.2%) was identified as A. niger, A. foetidus and A. tubingensis, and 11% of these isolates were OTA producers. A. niger was the most detected species in the wineries. However, only 5.3% of these isolates were ochratoxigenic. All the isolates of A. carbonarius obtained (22) produced the toxin, which highlights the importance of this species as the main source of OTA in grapes cultivated in Northeastern Brazil. OTA was detected in 13 (38.24%) samples analyzed with concentrations varying from 30.2 to 622.0 ng1-1. One white wine (obtained from the Vedejo variety) and Most of the red wine samples (75%) were contaminated by this toxin. OTA was not detected in any of the grape juice samples. The levels of OTA were below the maximum limit permitted in wine and juice according to the European Union (EU 123/2005).